Efficacy and safety of degarelix in patients with prostate cancer: Results from a phase III study in China - Yinghao Sun; Liping Xie; Tao Xu; Jørn S. Jakobsen; Weiqing Han; Per S. Sørensen; Xiaofeng Wang (Asian Journal of Urology)
Objective: To establish non-inferiority of gonadotropin-releasing hormone degarelix compared with goserelin in suppressing and maintaining castrate testosterone levels from Day 28 to Day 364 in Chinese patients with prostate cancer. Methods: This is an open-label, multi-centre study in which men aged ≥18 years were randomised in a 1:1 ratio to once-a-month subcutaneous injection of either degarelix (240/80 mg) or goserelin (3.6 mg) for 12 months. The primary endpoint was difference in 1-year cumulative probability of suppressing testosterone to ≤0.5 ng/mL. Non-inferiority was to be established if the lower 95% confidence interval (CI) limit for difference in cumulative probability between the treatment arms was greater than −10%. Secondary endpoints included cumulative probability of prostate-specific-antigen-progression-free-survival (PSA-PFS). Safety was also assessed. Results: Baseline demographics and disease characteristics were similar between degarelix (n=142) and goserelin (n=141) treatment arms. The difference in cumulative probability of maintaining castrate levels from Day 28–364 was 3.6% (95% CI:−1.5%, 8.7%), demonstrating non-inferiority of degarelix. The cumulative probability of PSA-PFS at Day 364 was higher for degarelix (82.3%, 95% CI: 74.7%, 87.7%) versus goserelin (71.7%, 95% CI: 63.2%, 78.5%, p=0.038). Adverse events (AEs) were similar between treatment arms, except for more injection site reactions with degarelix versus goserelin. Four (2.8%) and nine (6.4%) patients discontinued due to AEs in degarelix and goserelin groups, respectively. Conclusion: Degarelix was non-inferior to goserelin in achieving and maintaining testosterone suppression at castrate levels during 1-year treatment. PSA-PFS was significantly higher with degarelix, suggesting improved disease control. Both treatments were well tolerated.